2007
DOI: 10.1354/vp.44-3-373
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen Receptors α and β and Progesterone Receptors in Normal Bovine Ovarian Follicles and Cystic Ovarian Disease

Abstract: Abstract. The purpose of this study was to determine by immunohistochemistry the expression of estrogen and progesterone receptors in ovarian follicular structures from cows with cystic ovarian disease (COD) and to compare these with normal ovarian structures. Secondary, tertiary, atretic, and cystic follicles were evaluated. The follicular cysts of animals with COD presented a significantly higher expression of estrogen receptor a in all follicular layers than secondary, tertiary, and atretic follicles in bot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 23 publications
3
33
0
Order By: Relevance
“…Delayed follicle regression after ovulation failure is an alternative cause of cyst formation because a preovulatory follicle that cannot be ovulated will not grow further if it regresses immediately; therefore, no cystic follicles will be formed. In addition, we have previously described significant changes in steroid receptors, including the progesterone receptor (PGR) [62][63][64]. In this context, progesterone has been shown to stimulate granulosa cell differentiation [65,66].…”
Section: Discussionmentioning
confidence: 99%
“…Delayed follicle regression after ovulation failure is an alternative cause of cyst formation because a preovulatory follicle that cannot be ovulated will not grow further if it regresses immediately; therefore, no cystic follicles will be formed. In addition, we have previously described significant changes in steroid receptors, including the progesterone receptor (PGR) [62][63][64]. In this context, progesterone has been shown to stimulate granulosa cell differentiation [65,66].…”
Section: Discussionmentioning
confidence: 99%
“…However, there is disagreement as to its expression in ovarian cysts. Salvetti et al (2007) showed that no changes were observed in PGR protein expression in cystic follicles, whereas Alfaro et al (2012) described a higher expression of PGR mRNA, particularly the B isoform, in the theca cells of cystic follicles compared with healthy follicles. It was found that protein expression diminished in the granulosa cells, while it remained constant in theca cells.…”
Section: Steroid Receptor Coregulators In Bovine Codmentioning
confidence: 94%
“…However, ERα may also have redundant effects on granulosa cells, since ERβ single knockout mice were subfertile in contrast to ERα single knockout mice, which were infertile [17]. In bovine ovaries, granulosa cells were dominant cells that express ERα and ERβ [19], indicating the varied roles of estrogen receptors among species. In any case, estradiol is essential for normal folliculogenesis, whose target is likely to be granulosa cells.…”
Section: Estradiolmentioning
confidence: 99%